Exploration of the level and employment of ESL writing strategies among Malaysian lower secondary school students - Jacinta Karen Juin; Wardatul Akmam Din; Ameirul Azwan Ab. Aziz; Suyansah Swanto (Global Academic Excellence (M) Sdn Bhd, 2022)
This survey study explored and identified the level as well as the employment of ESL writing strategies use among Malaysian lower secondary school students. This study utilised Petric & Czarl (2003) modified writing strategies use questionnaire as its data collection instrument. 124 Form One students from an urban school in Keningau, Sabah participated in this study. The results of the questionnaire showed that lower secondary school students are medium users of writing strategies. The results also indicated that lower secondary school students used during writing strategies more than pre-writing and revising strategies. Recommendations for future studies include approaching related studies with qualitative approaches.